2018
DOI: 10.3892/etm.2018.6717
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography‑gated dual‑source computed tomography in the detection of atrial septal aneurysm

Abstract: The aim of the current study was to investigate the atrial septal aneurysm (ASA) incidence rate and describe its morphologic features by dual-source computed tomography (DSCT). A total of 8,626 patients (4,284 men and 4,342 women) who underwent DSCT examinations were enrolled. The presence of ASA was defined as the protrusion of the complete or partial interatrial septum with a maximum vertical distance (MVD) from the atrial septum plane of >10 mm during a cardiac cycle and a diameter of the aneurysm base of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In this modality, hypermobility of the interatrial septal can be measured during the cardiac cycle and a saccular interatrial aneurysm appears as a protrusion, often towards the atrium of lower pressure [7,24]. A cohort study of 8,626 patients with suspected coronary artery disease, found ASA in 51 (0.6%) patients using electrocardiograph (ECG)-gated CT [32]. Furthermore, CT can identify associated interatrial shunts.…”
Section: Computed Tomographymentioning
confidence: 99%
“…In this modality, hypermobility of the interatrial septal can be measured during the cardiac cycle and a saccular interatrial aneurysm appears as a protrusion, often towards the atrium of lower pressure [7,24]. A cohort study of 8,626 patients with suspected coronary artery disease, found ASA in 51 (0.6%) patients using electrocardiograph (ECG)-gated CT [32]. Furthermore, CT can identify associated interatrial shunts.…”
Section: Computed Tomographymentioning
confidence: 99%